Enhanced Porcine Reproductive and Respiratory Syndrome Virus Replication in Nsp4- or Nsp2-Overexpressed Marc-145 Cell Lines - Zhengqin Ye; Zhenbang Zhu; Liangzheng Yu; Zhendong Zhang; Xiangdong Li (Veterinary Sciences)
Porcine reproductive and respiratory syndrome (PRRS) causes significant economic losses to the swine industry. The killed PRRSV vaccine has been reported to be safe and could elicit humoral responses. The killed PRRSV vaccine with a high viral antigen load combined with robust adjuvants could provide good protection against the infection. However, the high virus titer of PRRSV on the successive production cell lines is the prerequisite for this strategy. In this study, we explored PRRSV production in two recombinant Marc-145 cell lines expressing Nsp2 or Nsp4 through a lentivirus system. The results demonstrated that either Nsp2 or Nsp4 expressing Marc-145 cells did not affect cell morphology and growth kinetics but significantly enhanced PRRSV replication. Overall, our exploration may enable the production of high-yield PRRSV and offer a potential tool for developing safer and more effective PRRSV vaccines.